EVALUASI MUTU SENSORIS DAN KIMIA IKAN ASAP BAUNG (Mystus Nemurus) YANG DIBUAT DARI IKAN SEGAR DAN BEKU - Hasan, Bustari; ', Sahyudi; ', Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was aimed to evaluate the sensory and chemical quality ofMystus smoked fish (Mystus nemurus) made from fresh and frozen fish. Mystusfish harvest size (200-300 grams) per head obtained from aquaculture cages inSungai Paku, Kampar. A total of 10 fish were frozen at -18 0C for 10 days beforesmoked and 10 other smoked in a fresh condition. Before the two fish groupssmoked, each cleaved form of butterfly like cut and filleted. Mystus fish thenwashed with clean water and smoked using multilevel temperature of 50-60 0C(drying), 80-95 0C (ripening) and 50-60 0C (improvement). The results showed asmoking yield of smoked fish fillets and butterfly like cut are made from freshfish are respectively 34.09% and 41.55% higher than made from smoked fish offrozen fish, which is 29.60% and 40.54%. Appearance and texture of smoked fishfillets and butterfly like cut are made from fresh fish better than smoked fish madefrom frozen fish, but the smell and the taste was not different between the twosmoked fish. Water content, fats and proteins of smoked fish are made from freshfish are respectively 15.00%, 18.60%, 44.08% and 15.79%, 18.93%, 43.65%;higher than that of water content, fats and proteins smoked fish are made fromfrozen fish, which is 14.66%, 18.13%, 43.59% and 15.59%, 18.46%, 43.31%.Keywords: smoked fish, quality, Mystus (Mystus nemurus), fresh fish, frozen fish.